Constitutive models for SPA-H weathering steel under coupled process and atmospheric corrosion - Weizhong Nie; Linfeng Lu; Hao Peng; Jichen Zhang (Frontiers in Materials)
This study simplifies the uniaxial tensile stress-strain curve of weathering steel and establishes degradation expressions for key mechanical properties, including elastic modulus, yield strength, ultimate tensile strength, fracture strength, and their corresponding strains, under single-side and double-sided corrosion, using mass loss rate and average corrosion depth as variables. Based on prior research, mathematical fitting was applied to the hardening and necking segments of the curve. Two constitutive models for SPA-H weathering steel under coupled corrosion were proposed, incorporating mass loss rate or average corrosion depth as the damage parameter. The models were validated against experimental data from this study, existing literature, and finite element simulations. Error analysis showed that the model based on average corrosion depth achieved higher accuracy than that based on mass loss rate. Reliability analysis further confirmed that both models are applicable when the design partial safety factor is ≥1.0. Moreover, a novel finite element method was developed by integrating the uniform corrosion approach with the equivalent material property method. Implemented in ABAQUS, this method effectively reproduced the uniaxial tensile behavior of all corroded specimens, demonstrating its feasibility and potential for engineering applications.